No se lo digas a Alfred - Mitford, Nancy, 1904-1973 (Libros del Asteroide, 2013)
Fanny is married to absent-minded Oxford don Alfred and content with her role as a plain, tweedy housewife with 'ghastly' clothes, but overnight her life changes when Alfred is appointed English Ambassador to Paris. In the blink of an eye Fanny's mixing with Royalty, Rothschilds and Dior-clad wives, throwing cocktail parties and having every indiscreet remark printed in tomorrow's papers.